Answer:
P( B∩ A₁ ) = 0.25
P( B∩ A₂ ) = 0.08
P( B∩ A₃ ) = 0.06
Step-by-step explanation:
As we know that
P( B∩ A₁ ) = P( B| A₁) × P(A₁)
P( B∩ A₂ ) = P( B| A₂) × P(A₂)
P( B∩ A₃ ) = P( B| A₃) × P(A₃)
As we have
P(A₁) = 0.50, P(A₂) = 0.20, and P(A₃) = 0.30.
P(B | A₁) = 0.50, P(B | A₂) = 0.40, and P(B | A₃) = 0.20
⇒P( B∩ A₁ ) = P( B| A₁) × P(A₁)
= 0.50(0.50)
= 0.25
⇒P( B∩ A₁ ) = 0.25
Now,
⇒P( B∩ A₂ ) = P( B| A₂) × P(A₂)
= 0.40(0.20)
= 0.08
⇒P( B∩ A₂ ) = 0.08
Now,
⇒P( B∩ A₃ ) = P( B| A₃) × P(A₃)
= 0.20(0.30)
= 0.06
⇒P( B∩ A₃ ) = 0.06
∴ we get
P( B∩ A₁ ) = 0.25
P( B∩ A₂ ) = 0.08
P( B∩ A₃ ) = 0.06